A biomechanical study of the movements of the arytenoid cartilage - Sellars, Ione (Division of Otorhinolaryngology, 2018)
The joint between the arytenoid cartilage and the cricoid cartilage is one of the smallest in the body. Its existence has been known since, if not before, the time of Galen (130-201 A.D.). However, little anatomical study has been carried out on this synovial joint and publications based on research into its exact anatomy and function are few. The results of these studies have been rarely questioned or scientifically re-examined, with the consequence that authoritative anatomical texts have perpetuated unconfirmed ideas of the behaviour of the cricoarytenoid joint. The purpose of this thesis is to present in detail the results of research into the anatomy and the functions of the cricoarytenoid joint and of the muscles that act upon it. This research began in 1977 with the dissection of 45 cadaver larynges. In this initial study the most striking anatomical finding was the identification of the so-called "posterior" cricoarytenoid ligament, of which inadequate and often incorrect detail has been presented in standard anatomy texts. Another surprising finding of this work was the variability of the shape and positions of the two cricoid facets. In 1978 these findings were published in detail (Sellars and Keen). An attempt to understand the accepted muscular control of the cricoarytenoid joint led to further research. This was carried out by the dissection of a further 23 larynges, with special care to examine the exact origin, direction and insertion of each muscle concerned. Six of these larynges, which had been surgically excised, were also stimulated electrically immediately after excision and the resultant arytenoid cartilage movements were recorded and analysed. The findings of this study were published in 1978 (Sellars) and these articles (Sellars and Keen, 1978; Sellars, 1978) are referred to in "Gray's Anatomy" and in Grant's "Method of Anatomy" (Sellars and Keen, 1978). Further examination of the reactions of these intrinsic laryngeal muscles to electrical stimulation has since been done on three additional fresh operative specimens. This additional work on laryngeal muscle action suggests that the explanation of specific intrinsic laryngeal muscle actions made in the earlier publication (Sellars, 1978) had been oversimplified. The main experimental work, on which this thesis is based, attempts to clarify and interpret the highly complex synchronized muscle actions that occur at the cricoarytenoid joint. Relevant facts found in both recent and old publications relating to this subject are presented and discussed. Before the review of literature is presented the embryology and basic anatomy of the larynx are described.